Multicenter Genomic Analysis of Carbapenem-Resistant Klebsiella pneumoniae from Bacteremia in China - Astrid V. Cienfuegos-Gallet; Ying Zhou; Wenxiu Ai; Barry N. Kreiswirth; Fangyou Yu; Liang Chen (Microbiology Spectrum, 2022)
ABSTRACT Klebsiella pneumoniae is one of the most common Gram-negative bacilli isolated from bloodstream infections worldwide, and recently an increased rate of carbapenem resistance has been reported in this pathogen. This study aims to describe the genomic characteristics of carbapenem-resistant K. pneumoniae (CRKP) isolated from patients with bacteremia in China. We analyzed 147 isolates from patients with bacteremia attended in 12 referral hospitals in China between April 2015 and November 2018. We conducted a phenotypic susceptibility evaluation and whole genome sequence analysis to characterize antimicrobial resistance profile, virulence genes, and dominant clones among CRKP. ST11 accounted for most infections (n = 98, 66.6%), followed by ST45 (n = 12, 8.2%), ST15 and ST290 (n = 8, 5.4% each). KPC (n = 98, 66.7%) and NDM (n = 27, 18.4%) are the main carbapenemases detected in the CRKP isolates. We detected yersiniabactin (n = 123, 83.7%) and aerobactin (49.9%) siderophores, and both rmpA and aerobactin genes in 21 ST11 isolates (21.43%), which are considered characteristic biomarkers of hypervirulent strains. Isolates showed high resistance rates to the β-lactams (>90%) and other antibiotics classes such as fluoroquinolones, aminoglycosides and tetracyclines (50%), but were susceptible to ceftazidime-avibactam (74.8%). In addition, we detected intra-hospital transmission of ST11 and ST45 strains in single and multiple wards in several hospitals, whereas inter-hospital transmission was relatively uncommon. In summary, we observed significantly genomic diversity of CRKP bacteremia isolates in China, although KPC-2 producing ST11 strains were found to be the most common clonal types. Reducing intra-hospital transmission remains to be the key to control CRKP caused bloodstream infections in China. IMPORTANCE K. pneumoniae is one of the most frequent Gram-negative bacilli isolated from bloodstream infections worldwide and recent studies have shown an increased rate of carbapenem resistance in China. Among carbapenem-resistant K. pneumoniae (CRKP) diverse clones have been reported, especially the high-risk clone ST11, which also exhibited a multidrug resistant phenotype. In addition to the antimicrobial resistance, previous studies have detected strains co-harboring virulent traits, highlighting the potential of transmission of both antimicrobial resistant and virulent strains. Here we studied the antimicrobial resistance profile, virulence genes and hospital transmission of CRKP from bacteremic patients in China. This study showed a high clonal diversity among CRKP, with the predominance of ST11 lineages. We detected virulence markers among multidrug resistant strains, and a high number of genetically similar isolates, suggesting intra-hospital transmission within single and multiple wards. Reducing intra-hospital transmission remains to be the key to control CRKP caused bacteremia in China.